Find the derivative of the function below.
h(w) = w^3ln(6w)
i keep coming up with the wrong answer...can someone tell me where im messing up
my answer: 3(ln(6w))^2+w^2
thanks
mathlete
In that case, you need to practice the product rule: $\displaystyle h=fg; h'=f'g+fg'$
$\displaystyle h(w) = w^3(ln(6w))$
$\displaystyle h'(w) = 3w^2(ln(6w)) + \frac{6w^3}{6w}$
$\displaystyle h'(w) = 3w^2(ln(6w)) + w^2$
It seems you either had a typo, or you misread something when applying the first term of the product rule.